Assessment the potential solar energy with the models for optimum tilt angles of maximum solar irradiance for Iraq. (December 2021) - Hassan, Qusay; Abbas, Majid K.; Abdulateef, Ammar M.; Abdulateef, Jasim; Mohamad, Abdulmajeed
Abstract: This work aims to assess the potential solar energy and determine the optimum tilt angles of maximum solar irradance in Iraq. The south-facing optimum tilt angle has been determined for eighteen cities of Iraq for estimation the solar radiation capacity. The optimisation process is performed by using hourly experimental solar radiation data for nineteen years. The results demonstrated that the maximum solar radiation can be collected with the tilt angle from 0° to 64°, where the optimum angle is evaluated/determined by searching for the values of the maximum total hourly-daily irradiance with the 1° resolution. The optimum tilt angle values increased during winter and decreased during summer, marking the highest values in January and December and the lowest values in June and July for all cities. The cities in the north of Iraq have higher optimum tilt angles values than those in the middle and south parts. Furthermore, a three general models are developed and validated for obtaining monthly and yearly optimum tilt angles positioning for estimation maximum irradiance.